REINTERPRETATION OF THE 100-DAY TAHLILAN PRACTICE WITHIN THE FRAMEWORK OF CONTEMPORARY ISLAMIC LEGAL THOUGHT - Akmal; Muhammad Asmar; Kurniati (Makkah: Journal Of Islamic Studies, 2025)
The tradition of tahlilan, particularly the practice of commemorating the 100th day after death, is a living phenomenon in Indonesian Muslim communities. This ritual is seen as a form of respect for the deceased as well as a means of strengthening social solidarity, but it has been criticized by some Islamic legal scholars because there is no direct recommendation for it in the texts of the Qur'an and Hadith. This study attempts to reinterpret the 100-day tahlilan practice from the perspective of contemporary Islamic legal thought, by examining the position of this tradition in classical Islamic law, contemporary responses to it, and the important role of the concepts of 'urf, bid'ah, and maqāṣid al-sharī'ah in determining the legitimacy of this practice. Using a normative-empirical qualitative approach, the study finds that tahlilan is strongly rooted as 'urf shahih in society as long as it does not conflict with sharia, and can be reviewed through the maqāṣid approach to develop accommodative contemporary ijtihad. These findings highlight the urgency of contemporary Islamic legal thought that is contextual and inclusive of local traditions within the framework of sharia.